Pediatric maxillofacial injuries and its management. Issue 1 (April 2021) - Rohit,; Vishal,; Prajapati, V.K.; Shahi, Ajoy; Prakash, Om; Ekram, Subia
Abstract: Background: Pediatric facial injuries are common due to children's high level of activity which gradually decreases as age advances. Main etiology in cases of pediatric age group are self-fall, sports related injuries, interpersonal violence and lastly road traffic accident. Pattern and management of facial fracture in pediatric age group is different to that of adult population. Material and methods: This study included 87 patients who had facial injuries and who reported at dental institute RIMS, Ranchi over a period of three years from 2017 to 2020. Initial assessment diagnosis and management were given to the patients. Results: Self-fall accounted as the leading cause of fracture (47.1%). Most frequent age group with facial injuries were from 7 to 12 years age group (49.1%). Dentoalveolar pattern of facial fracture was most common accounting for (39.1%) followed by mandible fracture in 33.3%. Closed reduction of the fracture was the most common way of treatment. Open reduction and fixation was carried out in 3.4% patients. Conclusion: Self-fall was the main etiology in our study and younger age group patients were more involved. Conservative treatment are generally given to pediatric age group, with open reduction in few cases on the basis of displacement. Close monitoring and follow up is mandatory in these age group.